Community Empowerment through an Integrated Waste Management System Based on Local Wisdom in Blahkiuh Village, Abiansemal District, Badung Regency, Bali, Indonesia - Ni Made Anggriyani; Anak Agung Putu Sugiantiningsih; Dewa Ketut Suryawan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The increasing volume of solid waste in Blahkiuh Village, Abiansemal District, Badung Regency, driven by population growth, residential expansion, and socio-economic activities, has created an urgent need for a more effective, participatory, and sustainable waste management system. The main challenges include the low rate of waste segregation at the household level, limited institutional capacity in community-based waste management, and the continued reliance on final disposal sites. This community service program aimed to strengthen the capacity of the village government and local community in developing an integrated waste management system based on local wisdom through improved governance, institutional strengthening, and active community participation. The implementation methods consisted of community outreach, capacity-building workshops, technical assistance in developing village regulations and Standard Operating Procedures (SOPs), the establishment of a community waste management working group, the implementation of a monitoring and evaluation system, and the formulation of sustainability strategies involving the village government, traditional village institutions, women's organizations (PKK), youth organizations, and community members. The program resulted in increased public awareness of waste segregation, the development of village regulations and SOPs for waste management, the establishment of a community-based waste management institution, and enhanced community participation through the application of the Tri Hita Karana philosophy. The program contributed to strengthening environmental governance, improving the quality of public services, and promoting a more sustainable community-based waste management system. Therefore, this empowerment model has the potential to serve as a best practice that can be replicated in other rural communities facing similar environmental challenges.